THE EFFECT OF PRODUCT QUALITY, SERVICE QUALITY, PRICE, AND TRUST ON PURCHASE DECISIONS (CASE STUDY ON SHOPEEFOOD USERS) - Vira Wilistyorini; Herry Sussanto (Asosiasi Dosen Muda Indonesia, 2022)
The purpose of this study is to analyze the effect of product quality, service quality, price, and trust on purchasing decisions either partially or simultaneously and to determine the variables are the most dominant on purchasing decisions on ShopeeFood in Bogor. The method of analysis in this study used a purposive sampling technique with data collection methods using questionnaires and the sample used 100 respondents. This study is a quantitative data types. The data analysis methods used are instrument test (validity test and reliability test), classical assumption test (normality test, multicollinearity test, and heteroscedasticity test), multiple linear regression analysis, t test, F test, and the coefficient of determination with statistical test using SPSS 25. The results of this study showed that in partially variables of product quality, service quality, price, and trust have a positive impact and significant effect on purchasing decisions. Meanwhile, variables of product quality, service quality, price, and trust simultaneously have a significant effect on purchasing decisions using ShopeeFood. And in this study, the most dominant independent variable on purchasing decisions is the price variable.